PENGARUH KONEKTIVITAS JARINGAN KERETA API TERHADAP PERTUMBUHAN EKONOMI REGIONAL DI PROVINSI JAWA BARAT - Iqbal Furqan, Muhammad
Train is one of the main modes of transportation as passenger and goods transportation. It was also stated in the National Railway Master Plan (RIPNAS) document that the railroad would be one of the modes of supporting transportation to support economic growth. According to PT. Kereta Api Indonesia (Persero), the number of train passengers in cities and between cities throughout Indonesia in 2018 totaled 423,846,257 people, an increase of 7.54% from the number of passengers in the previous year which was 394,134,634 people. As for the transportation of goods in 2018 it reached 45,236,310 tons, an increase of 12.92% from the volume of goods transported the previous year which was 40,060,714 tons. The increasing number of passengers has encouraged the government to continue to develop railroad infrastructure, both by the central and regional governments. The Ministry of Transportation's National Railway Master Plan (RIPNAS) document in 2010-2030 targets that the length of the inter-city railway network will reach 12,100 km by 2030 spread across the islands of Java-Bali, Sumatra, Kalimantan, Sulawesi and Papua, while the network length inner-city trains have a target of reaching 3,800 km. The rapid development and construction of the railroad network in Indonesia at this time is the proper momentum to examine the effect of railroad network connectivity on regional economic growth in West Java. This study adopted a model developed from earlier research conducted by Chong et al. (2019) with the conclusion that the development of high-speed rail (HSR) network connectivity in China has an important role in economic growth. This study conducted using multiple linear analysis methods with Gross Regional Domestic Product per Capita (GRDP per Capita) as a bound variable, Railway Network Connectivity as a free variable, as well as Government Investment per Capita, Private Investment per Capita, Human Development Index, Agricultural GRDP Ratio to GRDP, Industrial GRDP Ratio to GRDP, Services GRDP Ratio to GRDP, and Population as control variables. However, the specific results of this study showed different results, the coefficient of connectivity obtained ?2= -0,0008 which was statistically specific. These coefficients indicate that there is a negative influence of railroad network connectivity on regional economic growth.